Impact of Leverage on Profitability of Primary Aluminium Industry in India - Amsaveni, Dr. R. (Indian Journal of Finance, 2009)
The investment decision relates to the selection of assets in which funds will be invested by a firm. The finance decision is concerned with the selection of right mix of debt and equity in its capital structure. The third decision is related to the distribution of surpluses i.e. the dividend policy of the firm. Needless to say, the dividend decision is based on the success of the first two decisions, i.e. the investment and financing decisions. The tool leverage is used in the study to analyze the profitable proceedings of the Primary aluminium industry in India.